KEMAMPUAN MEMBACA PERMULAAN MENGGUNKAN METODE STRUKTURAL ANALITIK SINTETIK (SAS) KELAS I SDN 1 TRENCENG TULUNGAGUNG - Vita Aprila Soya; Nurna Listya Purnamasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reading is a fundamental skill that plays an important role in the learning process. Through reading, individuals can gather information, acquire knowledge, and gain new experiences. Early learning for students in lower grades of elementary school begins with early reading activities. Early reading is the initial stage for students in the process of recognizing letters, combining letters into words, arranging words into sentences, and understanding the meaning of those words. The purpose of this study is to describe early reading skills using the Structural Analytic Synthetic (SAS) method in first grade at SDN 1 Trenceng Tulungagung. This is a qualitative study with a descriptive approach. Data collection in this study used observation, tests, interviews, and documentation. The research results obtained the lowest average data: 1) the sentence reading indicator scored an average of 3.15 with a final score of 63, 2) the word reading indicator showed an average of 3.65 with a score of 73, 3) the syllable reading indicator had an average of 4 with a score of 80, 4) the letter reading indicator achieved the highest result, with an average of 4.3 and a score of 86. All four indicators achieved an average score of 75,5, indicating that the initial reading ability using the Structural Analytic Synthetic (SAS) method meets the “high” criteria and is considered good. Although it is considered good, the level of initial reading ability varies among students, so further improvements and enhancements are still needed in initial reading activities, particularly for lower-grade students.